Development of miliary tuberculosis under infliximab in a patient with spondyloarthritis and suspected Crohn’s disease = Entwicklung einer Miliartuberkulose unter Infliximab in einem Patienten mit Spondyloarthritis und vermutetem Morbus Crohn - Koschny, Ronald; Junghanss, Thomas; Mischnik, Alexander; Karner, Max; Kreuter, Michael; Roth, Wilfried; Stremmel, Wolfgang; Merle, Uta (Zeitschrift für Gastroenterologie, 2013)
Tuberculosis (TB) infection is a major concern in patients with chronic autoimmune conditions under immunosuppressive therapy. Gastrointestinal tuberculosis can be misdiagnosed as Crohn’s disease with detrimental consequences for the patient. We report on a 40-year old ethnic Turkish patient with HLA-B27 positive spondyloarthritis who developed gastrointestinal symptoms under immunosuppressive treatment with infliximab. Crohn’s disease was diagnosed at a primary care hospital and immunosuppressive treatment was escalated. Initial diagnostic tests for tuberculosis were negative. When the clinical condition deteriorated, the patient was transferred to our intensive care unit for further diagnosis and treatment. Tuberculosis was suspected due to clinical presentation and radiological signs and anti-tuberculous treatment was initiated. After the onset of treatment, first microbiological results confirmed the diagnosis of miliary TB with Mycobacterium bovis. As an infection route we assume primary gastrointestinal infection with M. bovis during the patient’s annual holidays in Turkey with a rapid development of miliary TB under infliximab and escalated immunosuppressive therapy. This case report demonstrates the difficulties in differentiating intestinal TB from other granulomatous conditions such as Crohn’s disease. The diagnostic tools for gastrointestinal tuberculosis are discussed in detail regarding their sensitivity, specificity as well as positive and negative predictive values.
Gesehen am 04.11.2021